Skilled labour immigration: A~vignette analysis on the willingness to accept migrants from outside the EU - Richard Wolff; Olaf Struck; Christopher Osiander (Journal for Labour Market Research, 2025)
Labour migration is of great economic and social importance. We use a factorial survey experiment to analyse under which criteria predominantly employed citizens approve of immigration of skilled workers from outside the EU to Germany. The criteria of the German Skilled Immigration Act for Qualified Professionals and procedural rules for checking qualifications as well as alternatives frequently discussed in the political sphere are taken into account. We find that the willingness to accept labour migrants is positively associated with (a) migrants having a definitive job offer, (b) holding (certified) professional qualifications and (c) the presence of skilled worker shortages in an industry. The vast majority of citizens favour the provisions of the act. They would also accept even less rigorous checks on qualifications.
Keywords: J08; J15; J18; J61; K37; 330; Factorial survey experiment; Labour market; Occupational closure; Online survey; Qualifications